Closed Shell Iron(IV) Oxo Complex with an Fe–O Triple Bond: Computational Design, Synthesis, and Reactivity. (29th October 2020) - Andris, Erik; Segers, Koen; Mehara, Jaya; Rulíšek, Lubomír; Roithová, Jana
Abstract: Iron(IV)‐oxo intermediates in nature contain two unpaired electrons in the Fe–O antibonding orbitals, which are thought to contribute to their high reactivity. To challenge this hypothesis, we designed and synthesized closed‐shell singlet iron(IV) oxo complex [(quinisox)Fe(O)] + (1 + ; quinisox‐H =( N ‐(2‐(2‐isoxazoline‐3‐yl)phenyl)quinoline‐8‐carboxamide). We identified the quinisox ligand by DFT computational screening out of over 450 candidates. After the ligand synthesis, we detected 1 + in the gas phase and confirmed its spin state by visible and infrared photodissociation spectroscopy (IRPD). The Fe–O stretching frequency in 1 + is 960.5 cm −1, consistent with an Fe–O triple bond, which was also confirmed by multireference calculations. The unprecedented bond strength is accompanied by high gas‐phase reactivity of 1 + in oxygen atom transfer (OAT) and in proton‐coupled electron transfer reactions. This challenges the current view of the spin‐state driven reactivity of the Fe–O complexes. Abstract : An iron oxo complex with an Fe≡O bond and a closed shell ground state was designed by employing DFT calculations, synthesized, and experimentally characterized by gas‐phase spectroscopic techniques. Despite the unprecedented Fe≡O bond strength and closed‐shell ground state, it still exhibits high‐reactivity.